Justification of the choice of hormone therapy for ovarian cancer - A.A. Mikhanovskyi; Yu.V. Kharchenko (Civic Union "Communicable Diseases Intensive Care Association", 2023)
BACKGROUND. Hormonal dependence of ovarian cancer remains a debatable issue in modern oncogynecology. Its decision will allow not only to clarify the pathogenesis of the development of ovarian cancer, its prognosis, but also to substantiate the indications for hormone therapy as a component of complex treatment. OBJECTIVE. To study the experience of domestic and foreign specialists regarding the pathogenetic rationale for prescribing hormone therapy to patients with ovarian cancer and its effectiveness. MATERIALS AND METHODS. Generalization and analysis of scientific publications on the research topic. RESULTS. The article summarizes data on the pathogenetic rationale for the appointment of hormone therapy, as well as the effectiveness of antiestrogens and aromatase inhibitors in the treatment of primary ovarian cancer and recurrences of the disease. CONCLUSIONS. To date, indications for the appointment and criteria for the use of hormone therapy in the complex treatment of ovarian cancer are not developed. The question of the reliability of the factors of the disease prognosis, taking into account the hormonal receptor status of ovarian cancer, remains open.